2009
DOI: 10.1021/jp808056x
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures of Cysteine-Coated CdS Nanoparticles Produced with “Two-Particle” Lithography

Abstract: There is an emerging need for practical methods that can produce organized arrays of nanomaterials with high throughput. Particle lithography provides such an approach for rapidly preparing millions of exquisitely uniform nanometer-sized structures on flat surfaces, using basic steps of bench chemistry. Structural templates of monodisperse latex or silica mesospheres can guide the deposition of nanoparticles to generate 2D arrays of nanopatterns with control of the surface coverage, size, and periodicity of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 90 publications
0
23
0
Order By: Relevance
“…51 Recent studies on functionalization of nanoparticles with cysteine have shown its interaction with different nanoparticles. 49,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Gawande et al, have successfully functionalized ferrite nanoparticles with cysteine and studied their application in multi-component reactions. 67 In their study, cysteine functionalized ferrite nanoparticles are used as a catalyst for the synthesis of derivatives of b-amino carbonyl compounds and hydroquinoline; and these nanoparticles are found to be highly reusable even after 9 cycles of reactions.…”
Section: Introductionmentioning
confidence: 99%
“…51 Recent studies on functionalization of nanoparticles with cysteine have shown its interaction with different nanoparticles. 49,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Gawande et al, have successfully functionalized ferrite nanoparticles with cysteine and studied their application in multi-component reactions. 67 In their study, cysteine functionalized ferrite nanoparticles are used as a catalyst for the synthesis of derivatives of b-amino carbonyl compounds and hydroquinoline; and these nanoparticles are found to be highly reusable even after 9 cycles of reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The shapes and surface density of gold nanoparticles and gold nanorods can be clearly resolved with SEM along the surface features of microlines. Dip-pen nanolithography (DPN) has been applied for direct surface patterning with nanoparticles of gold [39,53], iron oxide [38], cobalt [54], CoPt [55], CoFe 2 O 4 [55], CdS [50], BaFe [56], and metal-organic nanocrystals [57]. The processes for patterning and imaging nanopatterns prepared with DPN were accomplished ex situ.…”
Section: Spm-based Lithography With Nanoparticlesmentioning
confidence: 99%
“…The lattice parameters of the crystalline surface arrangement are depicted in figures 11b and 11c. An approach for "two-particle" lithography was reported by Lewandowski et al in which particles with different sizes and composition were mixed together to generate nanopatterns [50]. Two particle lithography was used to pattern cysteine-coated CdS nanoparticles (2 nm) on muscovite mica by evaporating a mixture of small CdS nanoparticles with silica spheres (500 nm).…”
Section: Arranging Nanoparticles On Surfaces Using Colloidal Lithographymentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we introduced several particle lithography-based protocols for patterning organosilanes using steps of vapour deposition, immersion or contact printing [51,52]. The surface selectivity of organosilane nanopatterns prepared with particle lithography approaches can be further applied to define the placement of other molecules and nanoparticles [53,54]. Particle lithography offers advantages for high-throughput patterning and enables control of the surface coverage, geometry and lateral dimensions of nanopatterns with relatively inexpensive reagents.…”
Section: Introductionmentioning
confidence: 99%